TEACHING FOREIGN LANGUAGES THROUGH INNOVATIVE METHODS - Mengliyeva, S (Innovative Development in Educational Activities, 2024)
this article explores how to use the interactive methods as well as the role of modern methods in teaching military terms and using them with examples during the lessons.